An Assessment of Fiscal Rules in the United Kingdom - Kell, Michael (IMF Working Papers; Working Paper ;, 2001)
The paper assesses the United Kingdom's golden rule and debt rule against "ideal characteristics" of fiscal rules. It concludes that they are clearly defined; transparent in institutional arrangements and measurement; adequate to ensure sustainability; and strike a good balance between flexibility and enforceability. The rules could be strengthened by clarifying the benchmark embodied in the debt rule and the modalities of the "value for money" criterion for investment. Overall, the fiscal framework establishes the necessary preconditions for a credible fiscal policy, but the credibility of the rules could be undermined by the large gap between them and actual medium-term fiscal plans.